Professor: Who holds the copyright for AI-assisted and AI-generated contents? - Zdravkova, Katerina (Language and Law / Linguagem e Direito, 2026)
Generative artificial intelligence has had a significant impact on intellectual property protection, mainly because model training is usually based on copyrighted content. This problem will deepen because, on the one hand, corporations with large training resources begin to sell contempt to AI companies, but also because authors whose copyrighted works are being used without permission react against this illegal theft. Parallel to this dilemma, a bigger one opens up: who is the copyright holder when artificial intelligence is an assistant in the creation of a work or when artificial intelligence has competently created a new work. The discussion of these issues is illustrated with the help of nine case studies, which are elaborated in more detail. Based on them, it becomes clear that works supported by artificial intelligence can become the author's works of persons whose creation was supported by AI, while competently autonomous works cannot be protected by any form of intellectual property protection.